Novel Laut Bercerita Karya Leila Salikha Chudori: Sebuah Studi Psikoanalisis - Prameswari, Irma; Pamungkas, Onok Yayang (CV. Eduartpia Publisher, 2024)
Psychological research often involves the object of human study. Meanwhile, not many psychological studies have focused on human objects in fiction. For this reason, the aim of this research is to explore aspects of human psychology in fiction, from Sigmund Freud's perspective. The research method uses a qualitative paradigm. The research data is in the form of discourse text which represents psychology. The data source is the Storytelling Sea Novel by Leila Salikha Chudori 42nd printing, issue of 2022. The results of the research show that the Storytelling Sea Novel represents three aspects of psychoanalysis: id, ego, and superego. The psychoanalytic aspect is dominated by the character Biru Laut, as the main character. The id aspect represents the main character's pure personality, without any external influences. Likewise the main character's ego, which is not influenced by external factors. The superego is influenced by social and family conditions. The three aspects of psychoanalysis are dominated by the superego aspect, this can be seen from the behavior and thought patterns of the Biru Laut characters which are dominated by social factors that influence them. Thus, id and ego are not always affected by external factors. Meanwhile, the superego still involves external influences as a subconscious driving factor for human attitudes. The implication of this research is that psychoanalytic classification turns out not only to the reality of life, but also to the reality of fiction. Apart from that, the implication of this research is to increase and develop interest in literary works in the form of reading such as novels, poetry and short stories so that it can broaden readers' insight regarding matters relating to literature. Keywords: Laut Bercerita Novel, Leila Salikha Chudori, Literature, Sigmund Freud, Psychoanalytic Studies